Professor Liu Liangli Treated 1 Case of Pulmonary Alveolar Proteinosis from Phlegm Stasis - Xiao, Tianmin; Liu, Liangli (Journal of Contemporary Medical Practice, 2025)
Pulmonary alveolar proteinosis (PAP) is a rare chronic interstitial lung disease, characterized by the accumulation of a large amount of phospholipoprotein-like substances in the alveoli and bronchioles. It lacks specific clinical manifestations and is mainly manifested as cough, expectoration, and dyspnea. In Western medicine, the main treatments include whole-lung lavage, inhalation/subcutaneous application of granulocyte-macrophage colony-stimulating factor, rituximab, pioglitazone, statins, gene therapy, plasma exchange, lung transplantation, etc. [1]. However, a unified treatment standard has not been established, and the disease cannot be completely cured. It can only relieve the clinical symptoms. Professor Liu Liangli, as a renowned traditional Chinese medicine doctor in Guizhou Province, has been engaged in the diagnosis and treatment of common and difficult respiratory diseases using integrated traditional Chinese and Western medicine for more than 30 years. Based on the theory of phlegm and blood stasis, she believes that the main pathogenesis of pulmonary alveolar proteinosis is the deficiency and decline of the internal organs as the root cause, and the obstruction of phlegm and blood stasis in the lungs as the superficial manifestation. Therefore, this disease mostly presents a situation of both deficiency of the root and excess of the branch, with a mixture of deficiency and excess syndromes. Among them, deficiency of the lungs, spleen, and kidneys is the main aspect. Therefore, in clinical practice, the principle of treating both the root cause and the superficial manifestation is adopted, and the treatment methods are to resolve phlegm and remove blood stasis, and to tonify the lungs, spleen, and kidneys, achieving good clinical curative effects.